LOCAL WISDOM VALUES AS THE FOUNDATION OF CIVIC DISPOSITION IN THE ETHNIC COMMUNITY OF BANJAR - Helda Yuliani , Karim Suryadi (Institut Agama Islam Ngawi, 2017)
ABSTRACT; This study aimed to discover local wisdom of Banjar ethnic particularly on women traders at Banjarmasin floating market. The research was carried out qualitatively toward the women traders at the floating market. The subjects of this research were the women sellers at floating market, the ethnic community of Banjar, academicians, and the local government. Data were collected by interview, observation, and documentation studies. The process of data analysis was conducted using a triangulation technique. This study discovered that basically the local wisdom of Banjar was formed and influenced by its geographical condition, which majority of people lives in riverside. Culture that they have was resulted from their experience of being close to the river and living with river culture for long time. These local wisdom, social condition and culture contain culture values which have transformed into certain dispositions or characters on their daily lives. There are high values which can be seen on the women traders' life. Honesty and humility values are shown from their words and acts on trading. These cannot be separated from religiousness of Banjar society of who mostly is Moslem.